ANALISIS GENESA BATUAN BEKU BERSTRUKTUR KEKAR TIANG MENGGUNAKAN DATA LAPANGAN DAN PETROGRAFI PADA DAERAH LEMAHABANG, DORO, PEKALONGAN, JAWA TENGAH - BAYU AJI SETIYAWAN; Oky Sugarbo (Retii, 2021)
The phenomenon of a geological object that is formed in the form of a columnar joint structure in the Lemahabang, Doro, Pekalongan, Central Java area is one of the formations of volcanic activity that happened in the past. Local community assumes that this phenomenon is an ancient relic in the form of megalithic site, but it can be explained scientifically through an analysis of the columnar joint characteristic by using field and petrografy data. The observasion by using quantitative and qualitative methods on rock samples in the research area showed that these rocks are andesite were afanitic-porphyritic textured with the type of colonnade and 4-7 facet formation with a diameter ranging from 30-87 centimeters. Columnar joint in the research area has dimention of 5 to 7 meters of height with a vertical orientation direction (80-90⁰) and horizontal orientation direction (0-30⁰). The purpose of this research is to provide an overview how columnar joint structure in Lemahabang can form so the local community doesn’t assume that the geological phenomenon is a tample.